Resistencia antimicrobiana y epidemiología molecular de aislamientos de Staphylococcus pseudintermedius de muestras clínicas de caninos - Vigo, Germán Blas (2015)
Twenty-eight strains isolated from dog clinical samples identified as Staphylococcus pseudintermedius by mass spectrometry (MALDI-TOF) were studied to assess antimicrobial sus-ceptibility by the diffusion method and clonal relationship by pulsed field gel electrophoresis(PFGE). Methicillin resistance (3/28 isolates; 10,7 %) was evaluated by mecA PCR. Fifteen strains(53.6 %) were resistant to at least one of the antibiotics tested, and eleven of them (39.3 %)showed multiple resistance (3 or more antimicrobial families). Eleven isolates (39.3 %) wereresistant to erythromycin due to the presence of ribosomal methylase ermB, whereas clindamy-cin inducible resistance was not detected. Twenty-seven (27) clonal types were differentiatedby PFGE, suggesting high clonal diversity. We emphasize that the finding of multiresistant S. pse-dintermedius strains is an emerging problem to be considered in veterinary diagnostic laboratorytreatment of canine infections and in public health settings.